Clerics and Scriptures: Experimentally Disentangling the Influence of Religious Authority in Afghanistan. Issue 2 (7th February 2017) - Condra, Luke N.; Isaqzadeh, Mohammad; Linardi, Sera
Abstract : This article unpacks the psychological influence of a Muslim cleric's power to mobilize for collective action in an experiment in Afghanistan. The same cleric requests contributions for a hospital from day laborers when dressed as a civilian and as a cleric. In Civilian condition, 50 per cent contributed and 17 per cent made large contributions; in Cleric condition, 83 per cent contributed but average giving did not increase as most gave the smallest possible amount. Inclusion of a recitation of Qur'anic verses in the Cleric condition maintains the 82 per cent contribution rate while increasing large contributions to 30 per cent, doubling average contributions. Formal education and subjective perception of poverty appear to drive the opposing effects of cleric and scripture. These results suggest that the power to activate spiritual channels lies in the scripture, not with the human wielding religious authority, who instead appears to induce minimal compliance with Islamic norms of charitable giving.